CROSSBREDING BETWEEN NATIVE CHIKEN AND LEGHORN CHIKEN STRAIN ISA BROWN - Safriyanto Dako; Safriyanto dako (Jurnal Peternakan, 2019)
This research is the first step, with aims to determine the production and reproduction ability of Crossbreding between male native chicken with female Isa brown strain leghorn, to be the parent in the next stage of research . This study used  3 male native chicken 12 -24 months of age. and  and 28 females of Leghorn chicken 14 month of ege,  with body weight 1100-1200 gram, crossbreding using artificial Insemination methode, semen domestic chicken dilution rate using physiological NaCl,  ratio sperm dilution 1 : 4. They were put in grower flocks with density of one birds per cage. Feeds during experiment were given in phases, starter Feeds  (Protein 21% and Energy 3000 kcal/kg), for layer (Protein 17% and Energy 2900 kcal/kg). Drinking water during experiment were given adlibitum. The result of the study illustrate crossbreeding between male native chicken and female leghorn chiken Isa Brown strain is  egg weight: 51.50-54.17 gram, egg index: 0.76 to 0.79%., Hatching weight: 39.34-39,39 grams, egg fertility 65,70-78,00%, hatchability 76.83-78.75%. In conclusion: egg weight of 52.42 eggs, egg index 0.78, eggs fertility 74.43%. hatchability 77,93%, and F1 body weight of 1 days of ege :  39.37 gram, and heritability DOC weight 0.43